Flexible Ionic Diodes with High Rectifying Ratio and Wide Temperature Tolerance. (26th March 2022) - Guo, Zi Hao; Wang, Hai Lu; Shao, Yangshi; Li, Longwei; Jia, Luyao; Pu, Xiong
Abstract: Soft iontronics expand the toolbox of bio‐integrated or bio‐interfaced devices, owing to their natural resemblance with living systems; however, the development for analogous integrated ionic circuits is immature due to the difficulty of fabricating fundamental ionic logic elements. Among these, ionic diodes have motivated great endeavors for their unique ionic current rectifying characteristics. Nonetheless, it is still challenging to achieve high‐performance ionic diodes; also, most reported aqueous solution‐based ionic diodes fail to work at extreme temperatures, seriously hindering their practical uses. This work reports a highly rectifying, temperature‐tolerant, and flexible hydrogel ionic diode enabled by an ethylene glycol/water binary solvent system. The ionic diodes exhibit outstanding dehydration resistance to high temperatures (100 °C) and anti‐freezing performance at low temperatures (−20 °C). Rectification ratios as high as 1201 (with 0% ethylene glycol content) and 566 (with 40% EG content) are achieved, which are distinctly advantageous over most previous reports. A flexible four‐diode bridge full‐wave rectifier circuit is then fabricated, and its integration with the triboelectric nanogenerator for effective biomechanical energy harvesting is demonstrated. This work is believed to open up new insights for the development of future bio‐interfaced applications. Abstract : A flexible ionic diode with high rectifying and wide temperature tolerance is fabricated in this work. An optimized rectification ratio as high as 1201 is achieved. The ionic diodes exhibit outstanding dehydration resistance to high temperature (100 °C) and anti‐freezing performance at low temperature (−20 °C). A full‐wave rectifier is then developed for applications in biomechanical energy collection.